Co-constructing skills for ChatGPT at university - McLeod, Amber; Richardson, Hannah (Journal of Academic Language and Learning, 2023)
This is a critical reflection on our teaching practice experiences using the generative AI tool, ChatGPT, in a Semester 1, 2023, fourth year digital technologies unit in an Australian University Initial Teacher Education program. We start with an outline of three pedagogical approaches where ChatGPT was embraced. We then draw upon our workshop observations and student assignments to provide insight into how students and educators used ChatGPT to co-construct technological knowledge and reinforce digital literacy. We conclude with reflections on the importance of explicit teaching and playful tinkering with ChatGPT to inform and support educators in building innovative teaching methods.